Ketamine, as adjuvant analgesics for patients with refractory cancer pain, does affect IL-2/IFN-γ expression of T cells in vitro?: A prospective, randomized, double-blind study. Issue 16 (April 2017) - Zhou, Naibao; Fu, Zhijian; Li, Hao; Wang, Kaiguo
Abstract: Background: Ketamine has been used as an analgesic adjuvant with morphine in the treatment of refractory cancer pain recently. But both morphine and ketamine have been reported to produce a number of immunomodulatory effects. The current study was performed to assess whether the concentration of ketamine, as adjuvant analgesics for patient with refractory cancer pain, was related to its effect on T cells interleukin-2 (IL-2)/interferon-γ (IFN-γ) expression in vitro. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from venous blood of patients with refractory cancer pain over a Ficoll-Hypaque density gradient. T cells were isolated from by positive selection using anti-CD3 beads. T cells were then treated with vehicle (C group), morphine (200 ng/mL, M group), morphine (200 ng/mL), and different dose of ketamine (100, 200, 1000 ng/mL; MK1, MK5, MK10 group) for 24 hours before stimulation with anti-CD3 and anti-CD28. Then supernatant IL-2 and IFN-γ protein analysis, quantitative reverse transcription polymerase chain reaction (RT-PCR) for IL-2 and IFN-γ were done. Results: There were no significant difference of supernatant IL-2 and IFN-γ among C group, M group, and MK1 group, but the mRNA of M group and MK1 group were decreased compared with C group ( P < .05). Compared with C group, both of the supernatant protein and the mRNA of MK5 group and MK10 group were all significantly decreased ( P < .01). Compared with M group, both of the supernatant protein and the mRNA of MK5 group and MK10 group were all decreased ( P < .05), while supernatant IL-2 and the mRNA of MK10 group were significantly decreased ( P < .01). Conclusion: In conclusion, we confirmed that just as morphine, ketamine dose-dependently suppressed IL-2 and IFN-γ of activated T lymphocyte of patients with refractory cancer pain in vitro, but the inhibitory action of low dose ketamine could be neglected.